2023
DOI: 10.1002/bab.2500
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structural characterization of exopolysaccharide from the Cordyceps cicadae and the immunomodulatory activity on RAW264.7 cells

Abstract: A new exopolysaccharide component named as PC‐EPS was isolated from Cordyceps cicadae, and its structure was determined. PC‐EPS was identified to be constituted of mannose, glucose, and galactose (28.84:1:19.42), with an average molecular weight of 3.72 × 106 Da, according to the results of monosaccharide composition, Fourier transform infrared, nuclear magnetic resonance, periodate oxidation and Smith degradation, and methylation studies. According to structural characterization, PC‐EPS's connection type was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Previous studies have shown that Cordyceps cicadae exopolyps significantly increase the phagocytosis and cell vitality of RAW264.7 cells and enhance its ability to produce TNF-α and IL-6, indicating that exopolysaccharide from the C. cicadae has the potential to improve the immunomodulatory activity of macrophages . Our results confirmed this.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that Cordyceps cicadae exopolyps significantly increase the phagocytosis and cell vitality of RAW264.7 cells and enhance its ability to produce TNF-α and IL-6, indicating that exopolysaccharide from the C. cicadae has the potential to improve the immunomodulatory activity of macrophages . Our results confirmed this.…”
Section: Discussionsupporting
confidence: 90%